2014
DOI: 10.1016/j.spinee.2014.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes are not different for patient-matched versus nonmatched treatment in subjects with chronic recurrent low back pain: a randomized clinical trial

Abstract: Background Classification schemas for low back pain (LBP), such as the Treatment Based Classification and the Movement System Impairment schemas, use common clinical features to subgroup patients with LBP and are purported to improve treatment outcomes. Purpose To assess if providing matched treatments based on patient specific clinical features led to superior treatment outcomes compared to an unmatched treatment for subjects with chronic, recurrent LBP. Study Design A randomized controlled trial. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 57 publications
1
41
1
1
Order By: Relevance
“…All questionnaires were self-administered and were identical at baseline and 1-, and 2-year follow-ups. Patient-reported outcomes instruments included the ODI low-back disability questionnaire, 4,7,15 SF-36, 21 and numeric rating scales for back and leg pain. 3,5,17 The ODI is a self-administered questionnaire that assesses back-specific function and contains 10 questions with 6 response categories.…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%
“…All questionnaires were self-administered and were identical at baseline and 1-, and 2-year follow-ups. Patient-reported outcomes instruments included the ODI low-back disability questionnaire, 4,7,15 SF-36, 21 and numeric rating scales for back and leg pain. 3,5,17 The ODI is a self-administered questionnaire that assesses back-specific function and contains 10 questions with 6 response categories.…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%
“…15,43,44 Apeldoorn et al 44 reported a mean baseline score of 6.06 on the NRS, which was lowered to 4.04 following 8 weeks of treatment with Delitto et al's TBC system. Our mean NRS scores were 3.43 at baseline and 0.23 at discharge, and were achieved within 1 month for most patients.…”
Section: Discussionmentioning
confidence: 99%
“…11 Because patient outcomes have improved when patients are provided a subgroup-matched treatment, 1,12-14 research on TBC systems for LBP has become a priority. 11,15 One TBC system, which has not been included in the 4 primary LBP classification systems, 11 is the MyoKinesthetic (MYK) System. The MYK System is used for a variety of musculoskeletal conditions, including LBP.…”
Section: Introductionmentioning
confidence: 99%
“…Stratified care , where patients are classified based on certain characteristics and then matched to appropriate treatment pathways, is one relatively simple and efficient method of targeting care 2 . Subgrouping approaches based on identifying common clinical features, usually within a single dimension (ie, pain characteristics, movement patterns, psychological profiles), have also been proposed as a way to target care 5 . Individualised care goes one step further with each person, as opposed to groups of people, receiving personally tailored care 1 3 4.…”
mentioning
confidence: 99%
“…Understandably, many clinicians are happier to focus within their own professional ‘comfort zone’, without exploring other domains. Consequently, most attempts at targeting care have adopted a relatively unidimensional subgrouping approach targeting only one or two domains (eg, physical factors or cognitive) 1 5. It could be argued that this may be adequate, as when one or two important aspects improve (eg, physical activity levels, and/or pain beliefs), the whole clinical picture (across multiple domains) may also improve.…”
mentioning
confidence: 99%